Different neuropathic pain syndromes in one patient – case reports - Dobrogowski, Jan; Kocot-Kępska, Lucyna (Contemporary Oncology/Współczesna Onkologia, 2008)
Neuropathic pain is initiated or caused by a primary lesion or dysfunction in the peripheral or central nervous system. The common causes of painful peripheral neuropathies are herpes zoster infection, diabetes mellitus, or not so common persistent postoperative pain, peripheral neuropathies, complex regional pain syndromes, phantom pain and central pain. As much as 0.5-0.8% of the population is affected. In the article two patients are described with neuropathic pain syndromes in the same location (patient RW) or at the same time (patient JP). Combined treatment including pharmacotherapy, neural blockades, neurodestruction techniques, psychotherapy and neuromodulation was initiated and 50% pain relief was achieved. The patients might be susceptible to neuropathic pain due to genetical conditions, but also applied chemotherapy might cause asymptomatic neuronal injury, and herpes zoster infection or surgical treatment was a determinant factor. The authors emphasize that special attention should be paid to patients treated with chemotherapy and afterwards operated on; also shingles prophylaxis should be considered.